Micronized Palmitoylethanolamide Ameliorates Methionine- and Choline-Deficient Diet–Induced Nonalcoholic Steatohepatitis via Inhibiting Inflammation and Restoring Autophagy - Hu, Jiaji; Ying, Hanglu; Yao, Jie; Yang, Longhe; Jin, Wenhui; Ma, Huabin; Li, Long; Zhao, Yufen (Frontiers in Pharmacology, 2021)
Nonalcoholic steatohepatitis (NASH) has become one of the serious causes of chronic liver diseases, which characterized with hepatic steatosis, hepatocellular injury, inflammation and fibrosis, and lack of efficient therapeutic agents. Palmitoylethanolamide (PEA) is an endogenous bioactive lipid with various pharmacological activities, including anti-inflammatory, analgesic and neuroprotective effects. However, the effect of PEA on nonalcoholic steatohepatitis is still unknown. Our study aims to explore the potential protective role of PEA on NASH and to reveal the underlying mechanism. In this study, the C57BL/6 mice were used to establish NASH model through methionine and choline deficient (MCD) diet feeding. Here, we found that PEA treatment significantly improved liver function, alleviated hepatic pathological changes, attenuated the lipid accumulation and hepatic fibrosis in NASH mice induced by MCD diet feeding. Mechanistically, the anti-steatosis effect of PEA may be due to the suppressed expression of ACC1 and CD36, elevated expression of PPAR-α and the phosphorylation levels of AMPK. In addition, hepatic oxidative stress was greatly inhibited in MCD-fed mice treated with PEA via enhance the expression and activities of anti-oxidant enzymes, including GSH-px and SOD. Moreover, PEA exerted a clear anti-inflammatory effect though ameliorate the expression of inflammatory mediators and suppress the NLRP3 inflammasome pathway activation. Furthermore, the impaired autophagy in MCD-induced mice was reactivated with PEA treatment. Taken together, our research suggested that PEA protects against NASH through the inhibition of inflammation and restoration of autophagy. Thus, PEA may represent an efficient therapeutic agent to treat NASH.